The effect of public health expenditure on infant mortality: Evidence from a panel of Indian states, 1983-84 to 2011-12 - Andrew J. Barenberg; Deepankar Basu; Ceren Soylu (University of Massachusetts, Department of Economics, 2015)
Using a panel data set of Indian states between 1983-84 and 2011-12, this paper studies the impact of public health expenditure on the infant mortality rate (IMR), after controlling for other relevant covariates like per capita income, female literacy, and urbanization. We find that public expenditure on health care reduces IMR. Our baseline specification shows that an increase in public health expenditure by 1 percent of state-level GDP is associated with a reduction in the IMR by about 8 infant deaths per 1000 live births. We also find that female literacy and urbanization reduces the IMR.
Keywords: E12; E20; 330; infant mortality rate; public health expenditure; female literacy; India